"Making do" in rural tourism: the resourcing behaviour of tourism micro-firms. Issue 7 (2nd July 2020) - Yachin, Jonathan Moshe; Ioannides, Dimitri
Abstract: We propose entrepreneurial bricolage as a framework that enables the description, explanation and exploration of the modus operandi of tourism micro-firms. Particularly, the notion of spatial bricolage constitutes fertile ground for further research and theoretical advances of sustainable tourism entrepreneurship. The potential for rural tourism development is conditioned by entrepreneurs' capability to utilise local physical and non-material resources sustainably. Thus, knowledge about the resourcing behaviour of micro-firms is paramount to understanding their role in promoting sustainable tourism. This study explores how rural micro-firms interact with their spatial environment to design tourism value propositions. Our analysis is based on interviews with eighteen owners-managers of tourism micro-firms in rural Sweden. We portray spatial bricolage as a resourcing behaviour that builds on the re-interpretation of existing resources, the unique features of the destination and community involvement. The findings suggest that resource transfer facilitates sustainable development since it enables long-term planning and validates the entrepreneurs' operation. Moreover, their small-scale enables rural tourism firms to utilise local resources in non-exploitative ways that minimise disturbance for other stakeholders.